Exosomes in cancer theranostic: Diamonds in the rough. Issue 2 (4th March 2017) - Cordonnier, Marine; Chanteloup, Gaëtan; Isambert, Nicolas; Seigneuric, Renaud; Fumoleau, Pierre; Garrido, Carmen; Gobbo, Jessica
ABSTRACT: During the last 10 years, exosomes, which are small vesicles of 50–200 nm diameter of endosomal origin, have aroused a great interest in the scientific and clinical community for their roles in intercellular communication in almost all physiological and pathological processes. Most cells can potentially release these nanovesicles that share with the parent cell a similar lipid bilayer with transmembrane proteins and a panel of enclosed soluble proteins such as heat shock proteins and genetic material, thus acting as potential nanoshuttles of biomarkers. Exosomes surface proteins allow their targeting and capture by recipient cells, while the exosomes' content can modify the physiological state of recipient cells. Tumor derived exosomes by interacting with other cells of the tumor microenvironment modulate tumor progression, angiogenic switch, metastasis, and immune escape. Targeting tumor-derived exosomes might be an interesting approach in cancer therapy. Furthermore, because a key issue to improve cancer patients' outcome relies on earlier cancer diagnosis (metastases, as opposed to the primary tumor, are responsible for most cancer deaths) exosomes have been put forward as promising biomarker candidates for cancer diagnosis and prognosis. This review summarizes the roles of exosomes in cancer and clinical interest, focusing on the importance of exosomal heat shock proteins (HSP). The challenges of clinical translation of HSP-exosomes as therapeutic targets and biomarkers for early cancer detection are also discussed.